2019
DOI: 10.3389/fendo.2019.00085
|View full text |Cite
|
Sign up to set email alerts
|

One Disease, Many Genes: Implications for the Treatment of Osteopetroses

Abstract: Osteopetrosis is a condition characterized by increased bone mass due to defects in osteoclast function or formation. In the last decades, the molecular dissection of osteopetrosis has unveiled a plethora of molecular players responsible for different forms of the disease, some of which present also primary neurodegeneration that severely limits the therapy. Hematopoietic stem cell transplantation can cure the majority of them when performed in the first months of life, highlighting the relevance of an early m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 89 publications
0
55
0
3
Order By: Relevance
“…In such cases, there are also reports that cochlear implants have been useful in patients with osteopetrosis who have deafness (17). Although osteopetrosis is genetically diverse, mutations in CSF1 have been reported as autosomal recessive in humans (18). In the present study, Csf1 op / op mice showed no nerve compression; therefore, hearing loss is thought to be largely due to conductive components such as spongy dysplasia of bone tissue in the ossicles and otic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, there are also reports that cochlear implants have been useful in patients with osteopetrosis who have deafness (17). Although osteopetrosis is genetically diverse, mutations in CSF1 have been reported as autosomal recessive in humans (18). In the present study, Csf1 op / op mice showed no nerve compression; therefore, hearing loss is thought to be largely due to conductive components such as spongy dysplasia of bone tissue in the ossicles and otic capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Because the bone marrow space is preserved by osteoclastic bone resorption within the bone, RANKL functions as a maintainer of the bone marrow and its indwelling immune cells. In most types of osteopetrosis, the patients exhibit mild to severe hematological defects, which can lead to anemia, hemorrhage, and severe or recurrent infectious diseases [55,56].…”
Section: Bone Marrow Formationmentioning
confidence: 99%
“…In addition, mild forms of TCIRG1 osteopetrosis have been recently identified in adult patients rising concerns about the risk of lifethreating complications during conventional therapy 41 . However, contrary to other inherited diseases treated with gene therapy 42 , the development of novel strategies is required in osteopetrosis to overcome clinical limitations that may hamper gene therapy applicability 43 . For this reason, we developed a tailored approach for the treatment of TCIRG1-mutated osteopetrosis exploiting autologous HSPC gene correction and expansion.…”
Section: Discussionmentioning
confidence: 99%